The role of psychological research in understanding and responding to links between climate change and conflict. (December 2021) - Suh, Se Min; Chapman, Daniel A.; Lickel, Brian
Summary: The impact of climate change on social conflict and violence is of increasing concern. The significant risk that climate change poses for human conflict has driven scholars to investigate the processes underlying the relationship. Although climate change may not directly cause conflict, heat waves and extreme weather events could amplify interpersonal violence, and climate change consequences (i.e. economic deprivation and migration) could also intensify intergroup conflict. However, psychological research is weakly integrated with this literature, and interdisciplinary efforts are needed to uncover the underpinnings of the relationship between climate change and conflict. In particular, psychological research on intergroup threat, climate change mitigation and adaptation, and culture can provide valuable insights into understanding and responding to climate-induced conflict. Highlights: Climatic variation is linked to increases in interpersonal and intergroup conflict. The link between climate change and conflict is heavily context dependent. Climate change will cause conflict through both direct and indirect pathways. Adaptation interventions may reduce the impact of climate change on conflict.